Pengaruh Variasi Putaran Motor Penggerak Terhadap Optimalisasi Kerja Pada Alat Shaking Table - Sore, Agustinus Seven; Jasron, Jahirwan Ut; Pah, Jack C.A.; Sanusi, Arifin (Universitas Nusa Cendana, 2024)
Indonesia is a country rich in minerals (mining), and iron sand is a source of magnetic material. The tool usually used in iron sand processing is the Shaking Table, a vibrating sieve mechanism that is generated by the force in the rotation of the driving motor for minerals such as metal and sand. This research aims to determine the rotation of the driving motor to obtain good material sieving results. From the test results of 3 kg of iron sand material, the best results were obtained at a rotation of 28.4 Rpm with the result of sieving material in the concentrate category as much as 0.55 kg and in the tailings category as much as 2.45 kg. The greater the pulley ratio, the slower the rotation that occurs on the wheel piston. On the other hand, the smaller the diameter of the pulley, the faster the piston wheel rotates to move the deck-shaking table. This occurs in accordance with the concept of moment of force, the pulley and axle are concentric wheels.